Implementation of knowledge engineering fundamentals in exercise science and individualization - Zaribafzadeh, H.; Dehaghani, R. A. (The Engineering of sport 7, Volume 2, 2008)
The evolution of traditional sports training, to the concept of exercise science, is attracting an ever increasing attention. A Systems approach to exercise science however, directs emphasis towards the concept of individualization. Individualization, however, poses challenging problems, when faced with the wide range of non-systematic definitions. The individualized approach to training tends to encompass information regarding the athlete, the sport is question and the equipment available. The ensuing and ideally, optimized training program, is governed by what might be termed as expertise exhibited by the coaching team in utilizing the training principles. A systematic implementation of the principles of training, however, requires a Systems approach to both "Experience" and "Knowledge". The ability to extract useful hidden know-ledge and to act on that knowledge is becoming increasingly important in today's competitive championship world. So, having a knowledge base along with a realistic decision making System could be considered a valuable asset and a useful tool for a coach. In this paper, the mechanism of the application of Knowledge Engineering fundamentals to both coach experience and sports training knowledge is discussed. The approach could be advanced to form an Expert System capable of making decisions towards organization of an optimized time oriented training program which is backed by both experience and elements of exercise science.